Synthetic microbiota for microplastic degradation modulates rhizosphere fungal diversity and metabolic function in highland barley - Deng, Yue; Xiang, Peng; Zhang, Mei; Wang, Shouqin; Zhou, Xudong; Liu, Jincheng; Li, Qiang; He, Guiqiang (Frontiers in Microbiology, 2025)
Microplastic (MPs) pollution is a growing concern for agricultural sustainability and crop nutritional quality. This study examined the individual and combined effects of polystyrene MPs (varying in particle size: <1 mm and 1–5 mm; and concentration: 1, 10, and 50 g/m2) and a synthetic microbiota consortium tailored for MP degradation (MPDSM) on the grain nutritional profile and rhizosphere fungal communities of highland barley. Application of MPDSM significantly enhanced MPs degradation, achieving a weight loss of 19.9% for large particles and 7.4% for small particles. MPs contamination reduced zinc content in grains, while particle size differentially modulated phytochemical composition: larger MPs increased flavonoid levels, whereas smaller MPs elevated polyphenol and vitamin E content. Notably, MPDSM treatment improved key nutritional indices, such as fat and vitamin C content. Moreover, the α-diversity of rhizosphere fungi increased under all treatments except under medium-concentration large MPs. The synthetic microbiota specifically enriched fungal diversity and drove community differentiation. FUNGuild analysis indicated a significant functional shift toward a Fungal_Parasite-Undefined_Saprotroph profile. These results demonstrate the potential of tailored synthetic microbiota to mitigate microplastic pollution in agroecosystems via remodeling the rhizosphere fungal community and its metabolic functions, presenting a promising bioremediation strategy for contaminated agricultural soils.